The political biogeography of migratory marine predators - Harrison, Autumn-Lynn; Costa, Daniel P.; Winship, Arliss J.; Benson, Scott R.; Bograd, Steven J.; Antolos, Michelle; Carlisle, Aaron B.; Dewar, Heidi; Dutton, Peter H.; Jorgensen, Salvador J.; Kohin, Suzanne; Mate, Bruce R.; et al. (Nature ecology & evolution, 2018)
During their migrations, marine predators experience varying levels of protection and face many threats as they travel through multiple countries’ jurisdictions and across ocean basins. Some populations are declining rapidly. Contributing to such declines is a failure of some international agreements to ensure effective cooperation by the stakeholders responsible for managing species throughout their ranges, including in the high seas, a global commons. Here we use biologging data from marine predators to provide quantitative measures with great potential to inform local, national and international management efforts in the Pacific Ocean. We synthesized a large tracking data set to show how the movements and migratory phenology of 1,648 individuals representing 14 species—from leatherback turtles to white sharks—relate to the geopolitical boundaries of the Pacific Ocean throughout species’ annual cycles. Cumulatively, these species visited 86% of Pacific Ocean countries and some spent three-quarters of their annual cycles in the high seas. With our results, we offer answers to questions posed when designing international strategies for managing migratory species. Daily location data on the individuals of 14 migratory marine species from 2000 to 2009 allow annual migratory cycles to be mapped to the time spent in the high seas and the exclusive economic zones of specific countries, providing a basis for international management strategies for these species.